2017
DOI: 10.3389/fimmu.2017.01857
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Activation in South African HIV-Exposed Infants Correlates with Ochratoxin A Exposure

Abstract: The introduction of non-breastmilk foods to HIV-infected infants is associated with increased levels of immune activation, which can impact the rate of HIV disease progression. This is particularly relevant in countries where mother-to-child transmission of HIV still occurs at unacceptable levels. The goal of this study was to evaluate the levels of the toxic food contaminant ochratoxin A (OTA) in HIV-exposed South African infants that are either breastfed or consuming non-breast milk foods. OTA is a common my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Earlier studies by this group of authors observed a remarkable increase in IYC exposure to AFs following the introduction of and increase in the consumption of weaning foods [34,126]. Similar results were reported in a South African study on non-breastfed infants [136]. Significant levels of OTA were detected in the plasma of non-breastfed infants at 6 weeks old as compared to breastfed infants.…”
Section: Mycotoxin Exposure Assessment Using Biomarkerssupporting
confidence: 86%
See 3 more Smart Citations
“…Earlier studies by this group of authors observed a remarkable increase in IYC exposure to AFs following the introduction of and increase in the consumption of weaning foods [34,126]. Similar results were reported in a South African study on non-breastfed infants [136]. Significant levels of OTA were detected in the plasma of non-breastfed infants at 6 weeks old as compared to breastfed infants.…”
Section: Mycotoxin Exposure Assessment Using Biomarkerssupporting
confidence: 86%
“…While cancer is rare in children, studies have linked exposures to environmental toxins in the perinatal period as a major causative agent of genetic diseases, such as cancer, in adulthood [210]. Thus, the frequency of mycotoxin occurrence in foods for infants and young children and mycotoxin exposure of this group, as highlighted in this review, should not be ignored [74,98,120,130,133,136].…”
Section: Causative Agent Of Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the mycotoxin ochratoxin A (OTA) mainly occurring in cereals, coffee, and red wine, has been reported to affect immunological response in piglets [43]. In humans, it is predominantly known for its acute nephrotoxic effect and a range of chronic disorders like upper urothelial carcinoma [44], but also immunomodulatory effects are under discussion [45].…”
Section: Immune Modulatory Potential Of Mycotoxinsmentioning
confidence: 99%